Poliembrionia em espécies de Bombacoideae (Malvaceae sensu lato) - Rodrigues, Clesnan Mendes (2005)
The presence of adventitious embryony and polyembryony has been documeníed for several species of Bombacoideae, although aspects of its ecological distribution, interspecific variation and influence on aspects of seed germination have been a little emphasized. The objective of the present study was to verify the occurrence of the polyembryony in different individuais of Eriotheca pubescens (Mart. & Zucc.) Schott & Endl. and Bombacopsis glabra (Pasq.) A. Robyns, its distribution in natural populations and the influence of morphological characteristics of the fruits on the polyembryony. It was also verified the interference of the polyembryony on the germination and emergency of polyembryonic seeds compared with some sexual species with monoembryonic seeds of the same group. The study was developed along the road between Uberlândia and Brasília, where fruits of individuais of Eriotheca pubescens were collected and had the number of embryos per seed, number of monoembryonic vs. polyembryonic seeds and fruit morphological characteristics evaluated. In a similar study accomplished with cultivated individuais of B. glabra in an urban areas, seeds were collected during the period from 2002 to 2004. Germination tests were carried out for the polyembryonic species and for individuais or species exclusively monoembryonic with E. pubescens (individuais with exclusively monoembryonic seeds), E. gracilipes (K. Sch.) A. Robyns, Pseudobombax longiflorum (Mart. & Zucc.) A. Robyns and P. tomenlosum (Mart. & Zucc.) A. Robyns. Seedling emergency was also observed in experimental conditions for the two embryonic patterns in E. pubescens measuring several characteristics of the germination and emergency process. E. pubescens and B. glabra presented seeds predominantly polyembryonic, but the frequency of polyembryony and average number of embryos per seed varied among fruits, individuais or even years of study. Individuais strictly monoembryonic represented only 13,16% of the individuais observed in E. pubescens and they had a more restricted geographical distribution. In the polyembryonic individuais, the frequency of monoembryonic seeds varied from zero to 48% and the average number of embryos per seed varied from 1,86 to 6,36. The two embryonic patterns in E. pubescens showed morphological differences among the characteristics of the fruits, but the analyses did not allow to separate clearly the two groups. In B. glabra individuais with strict monoembryony were not observed, but the number of embryos also varied among individuais and years. The polyembryonic seeds of E. pubescens presented lower germinability and vigor during initial growth than seeds from strictly monoembryonic individuais and than those of the other monoembrionic species. These differences may be associated to the competition for resources in polyembryonic seeds, but it is interesting to notice that even in the monoembryonic seeds of plants of E. pubescens with polyembryony, the vigor was lower than in seeds of the strictly monoembrionic individuais . These differences suggest that the strict monoembriony may be associated to sexual individuais in contrast with the predominance of the adventitious polyembryony associated to apomixis